Women and gender in Islam: Historical roots of a modern debate - Ahmed, Leila (Yale University Press., 1992)
Explores the historical roots of the debate about women in Islamic societies by tracing the developments in Islamic discourses on women and gender up to the present. The book describes the gender systems in place in the Middle East both before and after the rise of Islam.
Keywords: 1800-1899; 1900-1999; approches et analyses; asie; cours; cycles supérieurs; discipline; fem1000; fem7000; femmes* musulmanes; féminisme islamique; genre; histoire; identités LGBTQIA2+; islam; lit3220; moyen-âge; orient; premier cycle; périodes historiques; rapports de domination; rapports sociaux de sexe; religion; ressource en ligne; régions géographiques; science des religions; sciences humaines; sexisme; sociologie; syrie; systèmes d'oppressions; thématiques; théologie; voiles islamiques

The interpretation of the flesh: Freud and femininity - Brennan, Teresa (Routledge, 1992)
The 'riddle of femininity', like Freud's reference to women's sexuality as a 'dark continent', has been treated as a romantic aside or a sexist evasion rather than as a problem to be solved. In this first comprehensive study, Teresa Brennan suggests that by placing these ideas in the context of Freud's work as a whole, we will begin to understand why femininity was such a riddle for Freud. Brennan argues that by turning to Freud's work and his concrete questions about femininity, a psychical state which occurs in men and women alike, the problem is clearly a soluble one, provided that Freud's concern with energy is taken into account. The real riddle of femininity is as much a problem for thinking about physicality as a problem for the subject who suffers from what Freud described as 'femininity's negative effects on curiosity, intelligence and activity.
Keywords: 1900-1999; cours; discipline; fem1000; féminité; histoire; premier cycle; psychanalyse; psychologie; périodes historiques; ressource en ligne; sciences; sciences humaines; thématiques; violences

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (University of North Carolina Press, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Disponible en livre numérique et en format imprimé.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

La fabrique du sexe : essai sur le corps et le genre en Occident - Laqueur, Thomas Walter (Gallimard, 1992)
L'Occident n'a cessé depuis les origines de s'interroger sur la différence des sexes. Mais parle-t-on de l'homme et de la femme que l'on n'a encore rien dit : se réfère-t-on au genre - définition culturelle par des qualités morales, affectives, sociales... - ou au sexe - définition par des spécificités anatomiques ? Jamais, en effet, les deux notions ne se recouvrirent, rappelle Thomas Laqueur dans cet ouvrage qui demeure une référence majeure. Dès l'Antiquité, Aristote, par la définition de l'ordre des êtres, et Galien, par la définition du corpus anatomique, fondent le modèle du sexe unique, qui sera dominant jusqu'au XVIIIe siècle, et dans lequel le genre définit le sexe. Au XVIIIe siècle émerge l'autre modèle de la différence sexuelle, le modèle des deux sexes, dans lequel, au contraire du premier, le sexe définit le genre : parce que, au niveau de l'anatomie comme de la physiologie, femmes et hommes sont incommensurablement différents, les genres définissent dès lors qualités, vertus et rôles selon des racines biologiques. Ces deux modèles coexistent dans le temps - dès le XVIe siècle des auteurs posent l'irréductible différence anatomique, alors qu'au XXe siècle encore Freud pense la sexualité selon le modèle du sexe unique - car leur prégnance sur les esprits, si elle est liée à des évolutions générales - économiques, culturelles, sociales -, ne peut en aucun cas être strictement expliquée par celles-ci; et moins encore par les progrès de la connaissance anatomique, qui se moulent le plus souvent dans les représentations dictées par chacun de ces modèles...
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; corps; cours; discipline; discours dominant; essentialisme; féminisme matérialiste; genre; histoire; histoire et politique; hétérosexisme; occident; philosophie politique; premier cycle; production des savoirs; périodes historiques; sciences humaines; sciences sociales; sex1183; sex3383; sexe/genre; sexualité; systèmes d'oppressions; thématiques; épistémologie